Piperazine sulfonamides as DPP-IV inhibitors: Synthesis, induced-fit docking and in vitro biological evaluation - Khalaf Reema Abu; Alwarafi Ebtisam; Sabbah Dima (Acta Pharmaceutica)
Diabetes mellitus is a chronic illness that needs persistent medical attention and continuous patient self-management to avoid acute complications. Dipeptidyl peptidase-IV (DPP-IV) inhibitors minimize glucagon and blood glucose levels by increasing the incretin levels, glucagon-like peptide (GLP-1) and glucose-dependent insulinotropic poly-peptide (GIP), leading to insulin secretion from pancreatic beta cells. In the present study, nine 1,4-bis(phenylsulfonyl) piperazine derivatives 1a-i were synthesized and identified using 1H NMR, 13C NMR, MS and IR spectroscopies. These compounds were tested in vitro and showed inhibitory activity ranging from 11.2 to 22.6 % at 100 µmol L–1 concentration. Piperazine sulfonamide derivatives were found to be promising DPP-IV inhibitors, where the presence of electron-withdrawing groups such as Cl (1a-c) improved the activity of the compounds more than electron-donating groups such as CH3 (1d-f) at the same position. Additionally, meta-substitution is disfavored (1b, 1e, 1g). Induced-fit docking studies suggested that the targeted compounds 1a-i occupy the binding domain of DPP-IV and form H-bonding with the backbones of R125, E205, E206, F357, K554, W629, Y631, Y662 and R669.